Virtual Screening on Molecules Targeting the Interaction Between Estrogen Receptor Beta and Murine Double Minute 2 - Salmasfattah, Novyananda; Nurulita, Nunuk Aries; Dhiani, Binar Asrining (Indonesian Journal of Cancer Chemoprevention, 2022)
Estrogen receptor beta (ERβ) is an isoform of estrogen receptor that plays a role in breast cancer. An E3 ubiquitin ligase, murine double minute 2 (MDM2), can bind to ERβ and degrade it. Virtual screening and protein-protein docking studies are one of the approaches that can be performed to discover FDA-approved drugs targeting the interaction of the ERβ-MDM2 complex. This study aimed to conduct virtual screening of 1615 compounds targeting the interaction between ERβ-MDM2 as an initial study to discover potential breast cancer drugs. Biovia Discovery Studio 2021, ClusPro 2.0, PyRx 8.0, and PyMOL software were utilized in this study. ERβ (PDB ID: 3OLS) and MDM2 (PDB ID: 1T4E) receptors were docked to obtain the ERβ-MDM2 protein complex. The ligands used in the virtual screening were FDA-approved drugs downloaded from the ZINC database. PIC and PLIP web tools were also utilized to analyze the amino acid residues involved in the interaction. The virtual screening results showed that ergotamine was the drug with the lowest energy score (-12.0 kcal/mol) among 1057 drugs and was able to establish the strongest interaction between ERβ-MDM2. In conclusion, based on this computational study, ergotamine strengthens the interaction between ERβ-MDM2 and thus could be used as a candidate for breast cancer drug. Thorough validation of in vitro, biochemical, and in vivo studies are needed to confirm this finding.Keywords: Estrogen receptor beta, breast cancer, protein-protein interaction, MDM2.